Exclusive breastfeeding in preventing stunting in toddlers - Wa Ode Novi Angreni; Darmi Arda; Ari Setyawati; Anggun Sasmita; Indrawati Aris Tyarini; Nordianiwati Nordianiwati (Jurnal Edukasi Ilmiah Kesehatan, 2024)
Introduction: Exclusive breastfeeding during the first six months of a baby's life has been shown to have many health benefits, and one of them is that it can help prevent stunting in toddlers. Stunting is when a child's physical growth and brain development are hampered due to chronic malnutrition, especially protein, energy, and other essential nutrients. Objective: Know the role of exclusive breastfeeding in preventing stunting in toddlers. Methods: Type of quantitative analytical research with a case-control design using a retrospective approach. The population in this study was mothers who had toddlers aged 12–60 months, while the determination of subjects was based on simple random sampling techniques. The inclusion criteria were mothers with stunting toddlers aged 12–60 months and mothers willing to be respondents. The exclusion criteria are toddlers who suffer from chronic diseases and have a history of premature birth. The subjects in this study were 70 toddlers, consisting of 35 stunting toddlers as an intervention group and 35 non-stunting toddlers as controls. Results showed that toddlers who were exclusively breastfed and stunted were 15 (42.9%), while toddlers who were not exclusively breastfed and stunted were 20 (57.1%). Bivariate analysis showed an association between exclusive breastfeeding and the incidence of stunting (p-value 0.030). Conclusion: Exclusive breastfeeding can prevent stunting in toddlers. Exclusive breastfeeding can make a significant contribution to stunting prevention; other factors such as public health, sanitation, and access to nutrition also play an important role. Therefore, a holistic approach must be applied to support children's growth and development